Le confinement en croquis, vu de France. Géographie politique, sociale et culturelle du monde post-Covid19 - Jérôme Monnet (Cybergeo, 2020)
I propose here in a graphic and synthetic form a geographical analysis of the Great Containment, decreed in France from March to May 2020 as a measure to protect the population against the pandemic of the new coronavirus COVID-19. The successive sketches represent four major socio-spatial dimensions of containment, as implemented by the national government, experienced by the population at the neighbourhood and home scales, and deployed between users and service providers in the hyper-space that connects the place where communication devices are used with a wide variety of virtual perimeters, from near to far. The observation of the choices made by the State as well as dwellers’ tactics and social innovations in the face of containment leads to the identification of the main trends that could come into conflict during a crisis exit that is likely to be long and chaotic.